Economic evaluation from beef cattle production industry with intensification in Brazil’s tropical pastures - Romanzini, Eliéder Prates [UNESP]; Barbero, Rondineli Pavezzi; Reis, Ricardo Andrade [UNESP]; Hadley, David; Malheiros, Euclides Braga [UNESP] (Springer Nature, 2020)
This study aimed to evaluate different scenarios (year, supplementation level) about economic results of beef cattle production during rearing and finishing phase in Brazilian’s tropical pastures. Four scenarios were evaluated in combination with fourteen supplements, and it was originated from some research developed inside Forage Crops and Grasslands section from São Paulo State University among years 2011 and 2014. The economic evaluation was analyzed by operating cost, total operational costs, gross revenue, operating profit, and financial net income. Besides profitability, internal rate of return (IRR), benefit/cost ratio (B:C), and simple payback period (SPP) were calculated too. During rearing phase, the best result was observed for scenario 2 (2012), supplement 3.2 (mineral mix) with values of 11 cycles, 26.3%, 9.30%, and 0.39 for SPP, profitability, IRR, and B:C ratio, respectively. Already to finishing phase, the best scenario was 3 (2013), supplement 10 (multiple supplement with supplementation level equal 1.0% body weight), which obtained 4 cycles, 68.7%, 27.00%, and 2.34 for the same variables above mentioned. Results were consistent being that higher IRR and profitability occurred when using low supplementation level. Hence, the economic responses from different scenarios (years and supplements) can alter the final livestock farm financial statement.
Keywords: Dry season; Supplementation; Total operational costs; Wet season